2022
DOI: 10.1002/elsa.202100160
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐based guidance for improving CO2${\rm CO}_{2}$ reduction on silver gas diffusion electrodes

Abstract: The reduction of CO2${\rm CO}_{2}$ in an electrochemical reactor using electrical energy is a promising approach to implement a more sustainable carbon economy and to replace fossil fuels with renewable carbon sources. Conventionally used solid plate electrodes are limited by poor mass transport of the reactants. Gas diffusion electrodes (GDEs) can overcome this limitation and have gained industrial relevance during the last decades. A comprehensive understanding of transport and conversion phenomena within su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…They concluded that the decoupling of the electrochemical and microbial processes into separate reactors overcomes this limitation. Further modeling includes for example, the model‐based improvement of GDE (Heßelmann et al, 2022), model‐based upscaling of GDE based CO 2 ‐reduction systems (Z. Yang et al, 2021) and a multi‐criteria optimization of H 2 O 2 synthesis in GDE (von Kurnatowski & Bortz, 2021).…”
Section: Engineering Aspects—scale‐up and Modeling Of Gde‐based Proce...mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the decoupling of the electrochemical and microbial processes into separate reactors overcomes this limitation. Further modeling includes for example, the model‐based improvement of GDE (Heßelmann et al, 2022), model‐based upscaling of GDE based CO 2 ‐reduction systems (Z. Yang et al, 2021) and a multi‐criteria optimization of H 2 O 2 synthesis in GDE (von Kurnatowski & Bortz, 2021).…”
Section: Engineering Aspects—scale‐up and Modeling Of Gde‐based Proce...mentioning
confidence: 99%
“…They concluded that the decoupling of the electrochemical and microbial processes into separate reactors overcomes this limitation. Further modeling includes for example, the model-based improvement of GDE(Heßelmann et al, 2022), model-based upscaling of GDE based CO 2 -reduction systems (Z Yang et al, 2021). and a multi-criteria optimization of H 2 O 2 synthesis in GDE(von Kurnatowski & Bortz, 2021).6 | CONCLUSION AND OUTLOOKFor improvement of established production processes as well as development of new sustainable and biobased synthesis routes within a circular economy, the combination of biotechnology and electrochemistry is a powerful tool.…”
mentioning
confidence: 99%
“…[9,10] In the field of GDEs for CO 2 reduction, substantial work has been presented in the literature on catalyst design, [11,12] GDE composition, [13][14][15] and process studies on laboratory scale. [16][17][18] We recently presented a detailed model that predicts speciation and pH gradients for the reduction of CO 2 , [19] and investigated wetting in porous networks comprised of surfaces with different zeta potentials. [20] Although the fundamental Utilizing carbon dioxide (CO 2 ) as a resource for carbon monoxide (CO) production using renewable energy requires electrochemical reactors with gas diffusion electrodes that maintain a stable and highly reactive gas/liquid/solid interface.…”
Section: Doi: 101002/smll202204012mentioning
confidence: 99%
“…Indirect influences on the fluorescent lifetime might be changes in the local pH value, or the formation of ionic species on the electrodes as is often observed with CO 2 electroreduction. [19,42,43] This reaction visualization via FLIM allows the accurate identification of active areas of the GDE structure.…”
Section: Visualizing Of Reactions Inside a Gdementioning
confidence: 99%
“…Industrial CO 2 electrolyzers will require integration with upstream and downstream chemical processes. To plan for these deployments, chemical simulations must be able to accurately predict CO 2 electrolyzer behavior at relevant scales. Multiphysics simulations have been used to estimate reaction kinetics, model the pH distribution, improve CO 2 utilization, identify failure mechanisms, and provide a better fundamental understanding of lab-scale reactors. Most simulations of CO 2 electrolysis are one-dimensional simulations focused on single-carbon products with cell sizes <10 cm 2 (Table S5). Unfortunately, the computational expense of these simulations becomes prohibitive as the reactor grows due to the number of physical parameters and scales involved. , Models have been developed for CO 2 electrolyzers which are useful in predicting specific elements of electrolyzer performance (e.g., cell voltage) but do not produce a complete mass and energy balance .…”
mentioning
confidence: 99%